DETERMINAN PROFITABILITAS PERUSAHAAN PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN DI BEI - Amalia, Kiasatina; Kurniasih, Augustina (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2018)
The purpose of this research is to know and analyze Factors Affecting Company Profitability (Study on Food and Beverage Sector Listed on Indonesia Stock Exchange Period 2012-2015). This parametric statistical research method uses panel data regression analysis using Eviews Version 8. The number of samples that become the object of research as much as 13 companies of food & beverage sub sector. Sample selection method used is purposive sampling method. This method is based on criteria in the form of certain considerations used as a method of collecting samples. The result of the research shows that (1) The structure of the asset has positive and significant effect to Profitability, (2) Work Capital Turnover has positive and significant effect to Profitability, (3) Liquidity has positive and significant effect to Profitability, (4) Working Capital Funding has positive and significant to Profitability, and (5) Asset Structure, Working Capital Turnover, Liquidity, and Working Capital Funding contribute influence (R2) to Profitability. It is suggested that companies should pay attention to the use of shor-term debt in financing the company's operational activities so that the company's financial risk can be controlled and able to increase profitability.